2013
DOI: 10.1267/ahc.12029
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Glutamate and GABA during the Process of Rat Retinal Synaptic Plasticity Induced by Acute High Intraocular Pressure

Abstract: Acute high intraocular pressure (HIOP) can induce plastic changes of retinal synapses during which the expression of the presynaptic marker synaptophysin (SYN) has a distinct spatiotemporal pattern from the inner plexiform layer to the outer plexiform layer. We identified the types of neurotransmitters in the retina that participated in this process and determined the response of these neurotransmitters to HIOP induction. The model of acute HIOP was established by injecting normal saline into the anterior cham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…This indicates that there is a functional reduction of retinal neurons upon I/R injury. Two recent studies, also using the HIOP model in rats, reported the expression and distribution of SYPH after injury [5] , [38] and are consist with our findings of SYPH expression in the INL and OPL ( Fig. 3C ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This indicates that there is a functional reduction of retinal neurons upon I/R injury. Two recent studies, also using the HIOP model in rats, reported the expression and distribution of SYPH after injury [5] , [38] and are consist with our findings of SYPH expression in the INL and OPL ( Fig. 3C ).…”
Section: Discussionsupporting
confidence: 92%
“…3C ). Another study showed that synaptic plasticity can be induced by HIOP in retinas [5] . Therefore, the decrease of synapse-related proteins may also be connected to synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synaptophysin, a marker of presynaptic terminals, is widely used in the study of synaptic plasticity in the central nervous system and synaptophysin immunoreactivity has been considered to correlate well with synaptogenesis in the central nervous system[ 62 ]. Our previous studies demonstrated that high intraocular pressure-induced retinal injury could result in plastic changes of retinal synapses[ 4 11 63 ]: synaptophysin expression had a distinct spatiotemporal pattern from the inner plexiform layer to the outer plexiform layer and ultrastructure assay detected bouton-like vesicle-containing structures in the outer nuclear layer, however, the presynaptic changes were not accompanied by changes in the postsynaptic components. In this present study, the results of synaptophysin expression in the high intraocular pressure group and the sham surgery group were consistent with our previous study that synaptophysin expression in the inner plexiform layer was initially increased after high intraocular pressure injury and then synaptophysin distribution in the outer plexiform layer spread out, reaching as far as the inner outer nuclear layer with a peak at 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…The retinal tissue preparation was performed as previously described [20]. Briefly, the rats were sacrificed with excessive 2% pentobarbital solution intravitreal injection (80 mg/kg).…”
Section: Retinal Tissue Preparationmentioning
confidence: 99%